MRI-based morphometric analysis of corpus callosum dimensions in adults: Impact of age and gender in Kashmir (Panacea Journal of Medical Sciences, 2024)
Background: The Corpus callosum (CC) serves as the primary interhemispheric connection within the human brain, facilitating rapid information exchange and integration between the cerebral hemispheres, thus supporting complex cognitive functions. This study aims to explore the variations in corpus callosum (CC) dimensions across different age groups and genders, shedding light on the structural changes within this population.Materials and Methods: The present study was conducted within the premises of the Department of Anatomy, GMC Srinagar, spanning a duration of one year. During the study duration, a total of 5,921 images were meticulously reviewed, out of which 300 images met the stringent inclusion criteria and were consequently enrolled in the investigation. Measurements included fronto-occipital diameter, anteroposterior length, and dimensions of the genu, body, rostrum, and splenium.Results: The mean fronto-occipital diameter in the midsagittal plane was analyzed, revealing values of 163.21 ± 19.80 mm for males and 159.08 ± 22.8 mm for females. However, no statistically significant difference between genders was found (p = 0.08). The average anteroposterior length of the corpus callosum was measured at 74.81 ± 6.7 mm, with a height of 24.81 ± 1.03 mm. Additionally, the mean diameters of the genu, body, rostrum, and splenium were observed to be 10.8 ± 2.7 mm, 5.42 ± 2.9 mm, 3.79 ± 1.7 mm, and 10.79 ± 3.01 mm, respectively The analysis revealed significant age-related variations in CC dimensions, particularly in length (r = 0.389, p = 0.003), genu (r = -0.188, p = 0.02), height (r = 0.302, p = 0.004), and splenium (r = -0.387, p = 0.001). While no significant gender differences were observed in CC dimensions, age correlated positively with CC length and height but negatively with genu and splenium dimensions.Conclusion: These findings underscore the dynamic nature of CC morphology across the lifespan and highlight avenues for further investigation into the neurobiological mechanisms underlying these age-related changes.